The influence of folate supplementation on global gene expression in normal colonic mucosa of subjects with colorectal adenoma. Issue 4 (24th January 2013) - Pufulete, Maria; Abbadi, Reyad Al‐Ghnaniem; Arno, Matthew; Ewins, Mark; Green, Caroline; Astarloa, Estibaliz Aldecoa‐Otalora; Sanders, Tom; Emery, Peter; Ulrich, Cornelia M.; Miller, Joshua W.
<x xml:space="preserve">Abstract</x> Scope We determined whether short‐term supplementation with a physiological dose of folate alters global gene expression in the normal colonic mucosa of subjects with colorectal adenoma. Methods and results Fourteen subjects with adenoma, randomised to receive folic acid (400μg/day, n = 6) or placebo (n = 8) for 10 weeks, had blood samples and colonic tissue biopsies collected before and after the intervention. RNA extracted from colonic tissue samples was used to determine global gene expression in the colon using Affymetrix® Microarray GeneChips and real‐time RT‐PCR. Following intervention, 67 genes were upregulated and 13 genes were downregulated in the folic acid group, while 21 genes were upregulated and none were downregulated in the placebo group (p < 0.05, adjusted for multiple testing). Thirty‐six genes were upregulated and 18 genes were downregulated in the folic acid group when compared with placebo, but none of these were statistically significant after adjustment for multiple testing. These genes are involved in multiple pathways, including cell cycle, signal transduction, cell differentiation, transport, cell division, cell motility, protein transport, and immune response. Conclusion These results indicate that while folic acid can modify gene expression, it is difficult to separate its effects from the natural variability in gene expression in the colon.